The effect of protein and energy levels in diet on the antioxidant activity of juvenile redclaw Cherax quadricarinatus (von Martens, 1868) - Cortés-Jacinto, Edilmar; Campa-Córdova, Ángel I.; Ascencio, Felipe; Villarreal-Colmenares, Humberto; Holguín-Peña, Ramón J. (HIDROBIOLÓGICA, 2017)
This study determined the influence of dietary crude protein and energy levels on growth, survival, and antioxidant response of superoxide dismutase (SOD) in juvenile redclaw Cherax quadricarinatus. Six practical diets containing three crude protein (CP) levels (28, 35, and 40%) and two energy levels (~18 and 20 kJ·g1) were tested. The control group was fed a commercial shrimp diet. The highest SOD activity (34.8 U·mg1 protein) occurred in the diet with 35% CP and 18 kJ · g1. Soluble protein in tissue of redclaw fed 28 and 35% CP increased, compared to the control. The best mean final weight (9.23 g), weight gain (788%), and the lowest feed conversion ratio (1.3) occurred with the 35% CP diet. We conclude that a dietary CP content of 35% and 18 kJ · g1 is recommended for production and best immune responses in redclaw.